The anorexic voice and severity of eating pathology in anorexia nervosa. Issue 6 (15th February 2016) - Pugh, Matthew; Waller, Glenn
ABSTRACT: Objective: Internal "anorexic voices" are commonly described by individuals with eating disorders. This study examines whether the perceived power and nature of that voice are related to eating pathology in anorexia nervosa. Method: Sixty‐three women and one man with an ICD‐10 diagnosis of anorexia nervosa participated in this study (mean age = 27.3 years; mean BMI = 16.0). Participants completed questionnaires measuring severity of eating pathology, perceived voice power, and beliefs about voices, either at the start or during treatment. Results: A more powerful anorexic voice was associated with more negative eating attitudes in this clinical group. However, BMI was related to a moderating effect, with the interaction of greater voice power and malevolence being associated with a lower BMI. Discussion: These findings suggest the anorexic voice may function as a maintenance factor in anorexia nervosa. Cognitive models of hearing voices may be applicable to disorders other than psychosis. Further explorations are warranted. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:622–625).